2010
DOI: 10.1309/ajcpr1k0qflbjsnh
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Multicenter Evaluation of the BD GeneOhm VanR Assay for Direct, Rapid Detection of Vancomycin-Resistant Enterococcus Species in Perianal and Rectal Specimens

Abstract: The BD GeneOhm VanR assay (BD Diagnostics, San Diego, CA), a qualitative test for the rapid detection of vancomycin-resistant enterococci (VRE) from rectal and/or perianal swabs, combines integrated nucleic acid extraction and automated polymerase chain reaction for the detection of vanA and/or vanB gene sequences. We studied 1,027 perianal and rectal swab specimens from 3 geographically distinct US sites (prevalence rates, 13.1%-25.8%). Direct swab specimens were tested by the assay and compared with direct c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…The problem of low-level vancomycin resistance expression in vanB type enterococci has been known for a long time but has not been extensively studied or addressed until now, most probably due to its supposed low prevalence and thus moderate clinical significance ( Adler et al, 2010, Raponi et al, 2010and Rathe et al, 2010. The low predictive value for vanB VRE according to the results of VRE screening studies performed in countries of different continents was mainly addressed to the wide prevalence of vanB genes in nonenterococcal, intestinal colonizers ( Rathe et al, 2010, Stamper et al, 2007, Usacheva et al, 2010and Young et al, 2007. It has to be considered that a substantial number of vanB enterococci may have been missed in previous studies comparing the performance of real-time PCR-based screening assays against phenotypic comparator assays with a supposed low sensitivity in diagnosing vanB VRE with low-level vancomycin resistance expression (Werner et al, 2011b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of low-level vancomycin resistance expression in vanB type enterococci has been known for a long time but has not been extensively studied or addressed until now, most probably due to its supposed low prevalence and thus moderate clinical significance ( Adler et al, 2010, Raponi et al, 2010and Rathe et al, 2010. The low predictive value for vanB VRE according to the results of VRE screening studies performed in countries of different continents was mainly addressed to the wide prevalence of vanB genes in nonenterococcal, intestinal colonizers ( Rathe et al, 2010, Stamper et al, 2007, Usacheva et al, 2010and Young et al, 2007. It has to be considered that a substantial number of vanB enterococci may have been missed in previous studies comparing the performance of real-time PCR-based screening assays against phenotypic comparator assays with a supposed low sensitivity in diagnosing vanB VRE with low-level vancomycin resistance expression (Werner et al, 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of vanB type resistance by molecular methods circumvents the complications mentioned above with respect to a phenotypical measurement of resistance gene expression but conflicts with prevalence of vanB among nonenterococcal, intestinal colonizers ( Ballard et al, 2005, Domingo et al, 2005and Graham et al, 2008. The vanB gene prevalence in nonenterococcal, intestinal colonizers did not show a geographical preference and appeared at similar rates in different parts of the world as deduced from a number of clinical studies using real-time polymerase chain reaction (PCR)-based screening assays (Bourdon et al, 2010, Stamper et al, 2007, Usacheva et al, 2010, Werner et al, 2011band Young et al, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Usacheva et al (2010) compared the results of the BD GeneOhm™ VanR Assay with phenotypical tests only. Therefore their results may be biased by VRE with low MICs and are not comparable to our results.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to increased interest in screening of patients for colonization as well as to increased interest in methods used for a fast, sensitive, and reliable VRE detection (Vonberg et al, 2007). Rapid screening methods for VRE using direct polymerase chain reaction (PCR) from rectal swabs or stool have been described ( [Palladino et al, 2003], [Petrich et al, 1999] and [Satake et al, 1997]); some of these assays are commercially available ( [Bourdon et al, 2010], [Stamper et al, 2007], [Sloan et al, 2004] and [Usacheva et al, 2010]). These tests have been evaluated in a few studies performed, and excellent sensitivity and specificity for detecting vanA enterococci were shown, and a low specificity due to comparably high rates of supposed false-positive vanB samples appeared as a problem ( [Stamper et al, 2007] and [Sloan et al, 2004]).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular assays provide certain advantages over microbiological tests in terms of time, sensitivity and accuracy. Prevalence of van genes, especially vanB in intestinal, nonenterococcal species impairs performance of rapid, molecular screening assays targeting the corresponding resistance genes only (Stamper et al, 2007;Mak et al, 2009;Usacheva et al, 2010). Results of a number of studies performed with various commercially available diagnostic assays in Northern America, Australia, Asia and different countries in Europe also revealed that vanB is generally prevalent among human intestinal colonizers and that this is not a specific property of human intestinal colonisers in certain parts of the world …”
Section: The Van Alphabet In Intestinal and Environmental Bacteria Anmentioning
confidence: 99%